Corrosion Inhibition of Mild Steel in Hydrochloric Acid by 2-Benzoylpyridine and Pyridoxolhydrochloride. Issue 2 (2009) - James, A. O.; Oforka, N. C.; Abiola, O. K.; Ita, B. I.
Abstract : The inhibition of corrosion of mild steel in hydrochloric acid solutions by 2-benzoylpyridine (2BP) and pyridoxolhydrochloride (PXO) at 303K, 313K and 323K has been investigated using weight loss and hydrogen evolution techniques. 2BP exhibited higher maximum inhibition efficiency (78.99%) than PXO (71.93%). Generally inhibition was found to increase with increasing inhibitor concentration and decreasing temperature. A first order type of mechanism has been deduced from the kinetic treatment of the results and the process of inhibition was attributed to physisorption. The difference in the inhibition behaviour of the two compounds has been explained on the basis of structure dependent electron donor properties of the inhibitors